Determination of Decabrominated Diphenyl Ether in Soils by Soxhlet Extraction and High Performance Liquid Chromatography - Xing-Jian Yang; Zhi Dang; Fang-Li Zhang; Zhao-Ying Lin; Meng-Yao Zou; Xue-Qin Tao; Gui-Ning Lu (The Scientific World Journal)
This study described the development of a method based on soxhlet extraction combining high performance liquid chromatography (soxhlet-HPLC) for the accurate detection of BDE-209 in soils. The solvent effect of working standard solutions in HPLC was discussed. Results showed that 1 : 1 of methanol and acetone was the optimal condition which could totally dissolve the BDE-209 in environmental samples and avoid the decrease of the peak area and the peak deformation difference of BDE-209 in HPLC. The preliminary experiment was conducted on the configured grassland (1 μg/g) to validate the method feasibility. The method produced reliable reproducibility, simulated soils (n=4) RSD 1.0%, and was further verified by the analysis e-waste contaminated soils, RSD range 5.9–11.4%. The contamination level of BDE-209 in burning site was consistent with the previous study of Longtang town but lower than Guiyu town, and higher concentration of BDE-209 in paddy field mainly resulted from the long-standing disassembling area nearby. This accurate and fast method was successfully developed to extract and analyze BDE-209 in soil samples, showing its potential use for replacing GC to determinate BDE-209 in soil samples.